Advancements in Antioxidant-Based Therapeutics for Spinal Cord Injury: A Critical Review of Strategies and Combination Approaches - Yang-Jin Shen; Yin-Cheng Huang; Yi-Chuan Cheng (Antioxidants)
Spinal cord injury (SCI) initiates a cascade of secondary damage driven by oxidative stress, characterized by the excessive production of reactive oxygen species and other reactive molecules, which exacerbate cellular and tissue damage through the activation of deleterious signaling pathways. This review provides a comprehensive and critical evaluation of recent advancements in antioxidant-based therapeutic strategies for SCI, including natural compounds, RNA-based therapies, stem cell interventions, and biomaterial applications. It emphasizes the limitations of single-regimen approaches, particularly their limited efficacy and suboptimal delivery to injured spinal cord tissue, while highlighting the synergistic potential of combination therapies that integrate multiple modalities to address the multifaceted pathophysiology of SCI. By analyzing emerging trends and current limitations, this review identifies key challenges and proposes future directions, including the refinement of antioxidant delivery systems, the development of multi-targeted approaches, and strategies to overcome the structural complexities of the spinal cord. This work underscores the pressing need for innovative and integrative therapeutic approaches to advance the clinical translation of antioxidant-based interventions and improve outcomes for SCI patients.